Identification of equine in vitro metabolites of seven non‐steroidal selective androgen receptor modulators for doping control purposes. Issue 2 (10th December 2021) - Cutler, Charlotte; Viljanto, Marjaana; Taylor, Polly; Hincks, Pamela; Biddle, Simon; Van Eenoo, Peter
Abstract: Selective androgen receptor modulators, SARMs, are a large class of compounds developed to provide therapeutic anabolic effects with minimal androgenic side effects. A wide range of these compounds are available to purchase online and thus provide the potential for abuse in sports. Knowledge of the metabolism of these compounds is essential to aid their detection in doping control samples. In vitro models allow a quick, cost‐effective response where administration studies are yet to be carried out. In this study, the equine phase I metabolism of the non‐steroidal SARMs GSK2881078, LGD‐2226, LGD‐3303, PF‐06260414, ACP‐105, RAD‐140 and S‐23 was investigated using equine liver microsomes. Liquid chromatography coupled to a QExactive Orbitrap mass spectrometer allowed identification of metabolites with high resolution and mass accuracy. Three metabolites were identified for both GSK2881078 and LGD‐2226, four for LGD‐3303 and RAD‐140, five for PF‐06260414, twelve for ACP‐105 and ten for S‐23. The equine metabolism of GSK‐2881078, LGD‐2226, LGD‐3303 and PF‐06260414 is reported for the first time. Although the equine metabolism of ACP‐105, RAD‐140 and S‐23 has previously been reported, the results obtained in this study have been compared with published data. Abstract : Selective androgen receptor modulators (SARMs) are a large class of structurally diverse compounds developed to provide therapeutic anabolic benefits with minimal androgenic side effects. These compounds can be purchased online, and the potential performance enhancing effects associated with them presents a significant concern to doping control. The equine phase I metabolism of the SARMs ACP‐105, LGD‐3303, S‐23, GSK‐2881078, LGD‐2226, PF‐06260414 and RAD‐140 was investigated in vitro.